Hypoxaemia during recovery after surgery for colorectal cancer: a prospective observational study. (17th May 2019) - Bojesen, R. D.; Fitzgerald, P.; Munk‐Madsen, P.; Eriksen, J. R.; Kehlet, H.; Gögenur, I.
Summary: Episodic and ongoing hypoxaemia are well‐described after surgery, but, to date, no studies have investigated the occurrence of episodic hypoxaemia following minimally‐invasive colorectal surgery performed in an enhanced recovery setting. We aimed to describe the occurrence of postoperative hypoxaemia after minimally‐invasive surgery in an enhanced recovery setting, and the association with morphine use, incision site, fluid intake and troponin increase. We performed a prospective observational study of 85 patients undergoing minimally‐invasive surgery for colorectal cancer between 25 August 2016 and 17 August 2017. We applied a pulse oximeter with a measurement rate of 1 Hz immediately after surgery either until discharge or until two days after surgery, and recorded the oxygen saturation. We measured troponin I during the first four days after surgery, or until discharge. The median (IQR [range]) length of stay was 3 (2–4 [1–38]) days. Thirty‐six percent of patients spent more than 1 h below an oxygen saturation of 90% (4.2% of the day), and with a median (IQR [range]) proportion of 1.3 (0.2–11.1 [0.0–21.4])% of the day spent with an oxygen saturation below 88%. We found no associations between time spent below an oxygen saturation of 88% and morphine use (p = 0.215), fluid intake (p = 0.446), complications (p = 0.808) or extraction site (p = 0.623). Postoperative increases in troponin I were associated both with time spent below an oxygen saturation of 88% (p = 0.026) and hypopnoea episodes (p = 0.003). Even with minimally‐invasive surgery and enhanced recovery after surgery, episodic hypoxaemia and hypopnoea episodes are common, but are not associated with morphine use, fluid intake or incision site. Further studies should investigate the relationship between hypoxaemia and troponin increase.